2003
DOI: 10.1002/chin.200351044
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysis of Symmetrical Dithiobiurea and Thioureidoethylthiourea Derivatives.

Abstract: Ring closure reactionsRing closure reactions O 0130 Thermolysis of Symmetrical Dithiobiurea and Thioureidoethylthiourea Derivatives. -Microwave heating or pyrolysis of the title thiourea derivatives (I), (VI) and (IX) results in intramolecular heterocyclization processes furnishing various N,S-heterocycles. Application of microwave irradiation provides higher yields in comparison with yields obtained by thermal processes. -(HASSAN*, A. A.; MOURAD, A.-F. E.; EL-SHAIEB, K. M.; ABOU-ZIED, A. H.; DOEPP, D.; Hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…On adding tetrahydrofuran (THF) solution of 1,6‐disubstituted‐2,5‐dithiobiureas 4 to a solution of chloranil or bromanil 61a , 61b in the same solvent lead to the formation of thiadiazole derivatives 50 as a side product (Scheme ) [86].…”
Section: Reactions Of Dithiobiureas and Thioureidoalkylthioureasmentioning
confidence: 99%
See 3 more Smart Citations
“…On adding tetrahydrofuran (THF) solution of 1,6‐disubstituted‐2,5‐dithiobiureas 4 to a solution of chloranil or bromanil 61a , 61b in the same solvent lead to the formation of thiadiazole derivatives 50 as a side product (Scheme ) [86].…”
Section: Reactions Of Dithiobiureas and Thioureidoalkylthioureasmentioning
confidence: 99%
“…The interaction between 1,6‐disubstituted hydrazinearbothioamides 4 and chloranil 61 in THF led to the formation of 3‐substituted amino‐6,7‐dichloro‐1 H ‐benzo[ e ][1,3,4]thiadiazine‐5,8‐diones 123 (Scheme ) [86].…”
Section: Reactions Of Dithiobiureas and Thioureidoalkylthioureasmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have demonstrated that 4-substituted thiosemicarbazides 1a-c and 1,4disubstituted thiosemicarbazides 2a-c reacted with TCNE in ethyl acetate with admission of air to give products 3 and 4 (with 1a-c) and 5 and 6, in addition to the thiadiazole derivatives (with 2a-c) (Chart 1) [27,28]. CHART 1 Aldehyde semi-and thiosemicarbazones are polyfunctionalyzed compounds which easily cyclized by action of bases [7,8], acids [9], or oxidants [2][3][4][5][6]; therefore, they are useful and versatile synthons for the preparation of five-or six-membered heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%